Physical activity cardio-surgical patients - Stocka, Joanna; Stocka, Barbara; Szulc–Gackowska, Małgorzata; Siminska, Joanna; Grzyb, Sebastian; Szostak, Mateusz; Nowacka, Krystyna (Journal of Education, Health and Sport, 2017)
Health Behaviors are one of the most important factors that determine health. Physical activity plays an important role in the prevention of diseases i.e. hypertension, coronary artery disease, diabetes type 2, stroke and overweight and obesity. In the study this in the clinic of cardiac surgery University Hospital # 1 in Bydgoszcz in the period from October to November 2016 uses the International physical activity questionnaire (IPAQ). Encouraging patients coronary artery bypass grafting for physical activity before the procedure should be to educate patients about the importance of traffic before the operations and promote health promoting behaviors i.e.. correct diet and maintain a proper body weight, control blood pressure and glucose levels, and appropriate form traffic adapted to the needs and capabilities of the patient.